Consumption of Milk and alternatives decreased among Canadians from 2004 to 2015: evidence from the Canadian community health surveys - Hassan Vatanparast (BMC, 2021)
Abstract Background Milk and milk products make important contributions to the diet of Canadians. The aim of this study was to examine trends in Milk & Alternatives consumption among Canadians (≥2 years) from 2004 to 2015. Methods We used nutrition data from 2 nationally representative cross-sectional surveys conducted in 2004 and 2015 [Canadian Community Health Survey (CCHS) 2004 Cycle 2.2 and CCHS-Nutrition 2015] to compare Milk & Alternatives consumption between 2004 and 2015. Data from 24-h dietary recalls were collected using the Automated Multiple-Pass Method (AMPM). Result From 2004 to 2015, the proportion of Canadians consuming Milk & Alternatives food group significantly decreased from 89.5 to 87.7% and the number of servings consumed per day dropped from 1.9 to 1.7. Despite their low energy contribution (12.3% of energy), Milk & Alternatives contributed 45.8% of calcium, 39.9% of vitamin D, and 36.0% of vitamin B12 to the diet of the Canadian population in 2015. Milk & Alternatives were among the top sources of vitamin A, phosphorus and riboflavin. Milk & Alternatives food group was a major contributor to saturated fat intake in both 2004 (31.2%) and 2015 (28.6%). In 2015, dietary intakes of calcium and vitamin D among Milk & Alternatives consumers were 137.8, and 59.4% higher, respectively, than those of non-consumers. Conclusion Daily intake of Milk & Alternatives has decreased in the Canadian population over time, which may adversely affect the nutritional profile of the diet.